Adherence Trends in the Use of Innovative Drugs for Diabetes: Evaluation of Their Effectiveness and Safety - Hutapea, Dwight Mahaputera Marulitua (Oshada, 2025)
Type 2 diabetes mellitus continues to show increasing global and national prevalence, driving the need for more effective and personalized management approaches. Innovative therapies such as SGLT2 inhibitors and GLP1 receptor agonists present as pharmacological solutions with promising cardiovascular and renoprotective benefits. However, the effectiveness of these therapies in clinical practice is determined not only by drug efficacy, but also by patient adherence and health system readiness. This study used a qualitative approach based on literature review to evaluate the challenges of adherence as well as the effectiveness and safety of innovative therapies in type 2 diabetes. The results of the analysis showed that although innovative drugs have been proven effective in clinical studies, response variability and side effects in real practice require realworld evidence (RWE)based monitoring. Obstacles such as high costs, unequal access, and low patient understanding are major barriers to widespread implementation of therapy. Adherenceenhancing strategies, technologybased education, and inclusive financing policies are needed to optimize the benefits of therapy. Thus, successful diabetes management through innovative therapies requires an integration of scientific approaches, public policies, and active patient participation in a fair and responsive health care system.